2011
DOI: 10.1093/nar/gkr461
|View full text |Cite|
|
Sign up to set email alerts
|

Autoregulatory circuit of human rpL3 expression requires hnRNP H1, NPM and KHSRP

Abstract: Alternative pre-mRNA splicing (AS) is a major mechanism that allows proteomic variability in eukaryotic cells. However, many AS events result in mRNAs containing a premature termination codon, which are degraded by nonsense-mediated mRNA decay (NMD) pathway. We have previously demonstrated that human rpL3 autoregulates its expression through the association of AS with NMD. In fact, overexpression of rpL3 promotes downregulation of canonical splicing and upregulation of alternative splicing that produces an NMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…22 Furthermore, our previous results demonstrated that NPM is able to interact directly with rpL3, and that this interaction is functional to the regulation of the rpL3 protein levels inside the cells. 24 Data reported in this paper clearly demonstrate that NPM represents a positive regulator of rpL3-mediated transactivation of p21 gene, although it is not a crucial player in this event (Fig. 3).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…22 Furthermore, our previous results demonstrated that NPM is able to interact directly with rpL3, and that this interaction is functional to the regulation of the rpL3 protein levels inside the cells. 24 Data reported in this paper clearly demonstrate that NPM represents a positive regulator of rpL3-mediated transactivation of p21 gene, although it is not a crucial player in this event (Fig. 3).…”
Section: Discussionmentioning
confidence: 61%
“…To this purpose, a ChIp experiment in condition of mythramycin A (MTM) decay (AS-NMD). 24,25 In this paper, we demonstrate that rpL3 is a positive regulator of p21 expression. We show that rpL3 is able to modulate the protein amounts of p21 through a novel pathway independent from p53 involving Sp1 and NPM.…”
Section: Human Rpl3 Induces G 1 /S Arrest or Apoptosis By Modulating P21mentioning
confidence: 60%
See 1 more Smart Citation
“…25,36 We have previously reported that rpL3-mediated p21 upregulation requires the specific interaction between rpL3 and Sp1. 36 It has been shown that ERK1/2 is involved in p21 dependent G1 cell cycle arrest 37 and that ERK1/2 can phosphorylate Sp1 on Threonines 453 and 739 in vitro and in vivo. 21 These Sp1 phosphorylations were also detected when perifosine induced p21 CIP1 transcription via MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…of C. elegans rpl-3 and rpl-32, respectively, which catalyze their own splicing in a post-transcriptional feedback circuit (Vilardell and Warner 1997;Russo et al 2011). Regulation by nonsense-mediated decay is also common (Cuccurese et al 2005).…”
Section: Discussionmentioning
confidence: 99%